Urgensi Pelindungan Indikasi Geografis Tembakau Lamsi Temanggung untuk Menjaga Keaslian dan Kualitas Produk Berdasarkan UU Nomor 20 Tahun 2016 - Christina Basanova Sidabalok; Miranda Risang Ayu Palar; Helitha Novianty Muchtar (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study explores the importance of protecting the Geographical Indication (GI) of Lamsi Tobacco from Temanggung to safeguard its authenticity and maintain product quality, in accordance with Law Number 20 of 2016 on Marks and Geographical Indications. Lamsi Tobacco is known for its distinctive taste, aroma, and quality, which are influenced by the geographical conditions of Temanggung as well as traditional cultivation practices passed down through generations. However, without legal protection, the authenticity and reputation of this product risk being diminished due to counterfeiting or unauthorized use of its name. The research method employed is normative juridical, which focuses on library research or secondary data by viewing law as a set of written norms enacted by authorized institutions. To strengthen the analysis, this study is also supported by a socio-legal approach that combines legal studies with social sciences so that law is understood not only as written norms but also as a practice that lives within society. The findings indicate that Lamsi Tobacco meets the criteria for Geographical Indication as stipulated in Law No. 20 of 2016 Protection through Geographical Indications not only plays a role in preserving the authenticity and quality of the product but also generates positive economic and social impacts for the community, particularly farmers. Nevertheless, several obstacles remain, such as low legal awareness, administrative difficulties, and the absence of a strong managing institution. Therefore, coordination between the central government, local government, farmer associations, and the community is necessary to realize effective legal protection. Through the registration and protection of Geographical Indications, Lamsi Tobacco is expected to maintain its reputation, increase competitiveness in the market, and make a tangible contribution to the welfare of the Temanggung community as well as the preservation of local culture.